2019
DOI: 10.1002/joc.6288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some distributional downscaling methods as applied to daily maximum temperature with emphasis on extremes

Abstract: Statistical downscaling methods are extensively used to refine future climate change projections produced by physical models. Distributional methods, which are among the simplest to implement, are also among the most widely used, either by themselves or in conjunction with more complex approaches. Here, building off of earlier work we evaluate the performance of seven methods in this class that range widely in their degree of complexity. We employ daily maximum temperature over the Continental U.S. in a “Perfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…As stated by Wang and Chen (2014), EDCDFm may be meaningless when an unmatched theoretical distribution is used. For the ECDF method, Mcginnis et al (2015) found that the KDE approach performs better than ECDF, whereas Lanzante et al (2019) found no significant difference between their performances. The current study found ECDF method and DKDE method are equally skilful (Sections 3.2 and 3.3), which is also confirmed using different sample sizes (Figure S2).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As stated by Wang and Chen (2014), EDCDFm may be meaningless when an unmatched theoretical distribution is used. For the ECDF method, Mcginnis et al (2015) found that the KDE approach performs better than ECDF, whereas Lanzante et al (2019) found no significant difference between their performances. The current study found ECDF method and DKDE method are equally skilful (Sections 3.2 and 3.3), which is also confirmed using different sample sizes (Figure S2).…”
Section: Discussionmentioning
confidence: 96%
“…In a realistic climate condition, the internal variability, especially the internal low-frequency variability, can bring uncertainty (Maraun and Widmann, 2018;Chen et al, 2020). A better framework would be the pseudo-realistic approach which can provide a more rigorous evaluation of the stationarity hypothesis (Lanzante et al, 2018(Lanzante et al, , 2019. (b) The corrected results largely depend on the output of the raw climate model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, this author team, members of the Geophysical Fluid Dynamics Laboratory (GFDL) Empirical Statistical Downscaling (ESD) team (https://www.gfdl.noaa.gov/esd_eval) has focused on evaluating some of these techniques. For an SD overview and our evaluation approach philosophy see our earlier works and cited references (Dixon et al ., 2016; Lanzante et al ., 2018; Lanzante et al ., 2019a, hereafter L19a; Lanzante et al ., 2019b, hereafter L19b). As a caution we note that even the best SD methods will fail to produce credible results if the driving physical climate model is flawed in its representation of circulation features (Hall, 2014; Maraun et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%